Improved Hepatic Gene Transfer by Using an Adeno-Associated Virus Serotype 5 Vector - Mingozzi, Federico (American Society for Microbiology, 2002)
Adeno-associated viral (AAV) vectors have been shown to direct stable gene transfer and expression in hepatocytes, which makes them attractive tools for treatment of inherited disorders such as hemophilia B. While substantial levels of coagulation factor IX (F.IX) have been achieved using AAV serotype 2 vectors, use of a serotype 5 vector further improves transduction efficiency and levels of F.IX transgene expression by 3- to 10-fold. In addition, the AAV-5 vector transduces a higher proportion of hepatocytes (∼15%). The subpopulations of hepatocytes transduced with either vector widely overlap, with the AAV-5 vector transducing additional hepatocytes and showing a wider area of transgene expression throughout the liver parenchyma.